Liberalism and Its Implication for African Thought in the 21st Century: A Critical Analysis - Asuquo, Gabriel (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
This paper critically analyzes the philosophical foundation of liberalism and its implications for African thought in the 21st century. The authors locate liberalism as an outgrowth of Western individualism which upholds the idea of individual freedom, autonomy, and equality. This in turn has an adverse implication for African thought that emphasizes communalism and interpersonal relationship. The author traces the philosophical foundation of liberalism in the philosophies of John Locke and Thomas Hobbes and outline African thought from the philosophical works of Innocent Asouzu and Chiedozie Okoro. This paper argues that the foundation of African thought on duality, complementarity, and its principle for socialization is located in communalism. Therefore, the paper sees liberalism with its attendant ontology of monism as a challenge in which African thought of communalism and pluralism should rehabilitate and integrate for mutual enrichment. Hence, for this to happen the authors maintain that liberalism and African thought constitute a 'missing link' that are to be opened for mutual complementation. This will foster the advancement of human civilization and the building of a just world order in the 21st century. The philosophical implication therein is that all absolutist thoughts and institutions in which liberalism is championing in politics, economic, education, and social re-engineering should be harmonized within the African thought of complementarity. The authors employ the method of critical analysis.